Direct observation of chiral edge current at zero magnetic field in a magnetic topological insulator - Jinjiang Zhu; Yang Feng; Xiaodong Zhou; Yongchao Wang; Hongxu Yao; Zichen Lian; Weiyan Lin; Qiushi He; Yishi Lin; Youfang Wang; Yongqian Wang; Shuai Yang; et al. (Nature Communications)
Abstract The chiral edge current is the boundary manifestation of the Chern number of a quantum anomalous Hall (QAH) insulator. The van der Waals antiferromagnet MnBi2Te4 is theorized to be a QAH in odd-layers but has shown Hall resistivity below the quantization value at zero magnetic field. Here, we perform scanning superconducting quantum interference device (sSQUID) microscopy on these seemingly failed QAH insulators to image their current distribution. When gated to the charge neutral point, our device exhibits edge current, which flows unidirectionally on the odd-layer boundary both with vacuum and with the even-layers. The edge current chirality reverses with the magnetization of the bulk. Surprisingly, we find the edge channels coexist with finite bulk conduction even though the bulk chemical potential is in the band gap, suggesting their robustness under significant edge–bulk scattering. Our result establishes the existence of chiral edge currents in a topological antiferromagnet and offers an alternative for identifying QAH states.